The Influence of Reading Fondness Characters on Students' Attitudes in Science Subjects in Junior High Schools - Muhammad Sofyan Zain; Astalini Astalini; Dwi Agus Kurniawan (Indonesian Journal Of Educational Research and Review, 2021)
Many students have a low level of reading pleasure. This will have an impact on common science learning outcomes for students. Reading fondness has been known to improve students 'cognitive domains, what about students' attitudes, namely the affective domain? The purpose of this study was to measure the effect of reading fondness on attitudes in science subjects in junior high schools. The schools studied consisted of 1 private school and 2 public schools with a total sample of 411 students. The sampling technique was cluster sampling. The research method used is quantitative with simple linear regression analysis and descriptive statistical analysis. The instrument used was a valid and reliable questionnaire for reading fondness and attitudes towards science. The results of this study indicate that students' reading pleasure is in the good category, the attitude towards science is in the good category This research implies that students' reading habit has a positive influence on science.